Paleobotanical study of the fossiliferous locality of the Santa Rosa de Sexi district (Middle Eocene), Santa Cruz province, Cajamarca department, Peru - Prado Velazco, Ysabel (2016)
The fossil forest known as shaman stone, is located in the Andes of northern Peru, at 79 ° 10 ’west longitude and 6 ° 35’ south latitude. It is the most diverse association of fossil plants in Peru, made up of fossil stems and leaves preserved by ash and lahar deposits from the Huambos Formation. This formation was dated by the 40Ar / 39Ar method (39 million years old) from the Middle Eocene. The existence of numerous unidentified fossil stems, coming from the Santa Rosa de Sexi district, preserved in the geosciences division of the Natural History Museum of the National University of San Marcos was the incentive to study them and determine the type of logs; reason why the objective of this work is to identify the taxa, based on the paleomicromorphological study of the stem anatomy of the samples. 7 species have been reported, of which 6 are Magnoliopsids; belonging to 4 families: Apocynaceae family (Aspidosperma parvifolium and Tabernaemontanasp.); Fabaceae family (Copaifera officinalisy Prosopis chilensis); family Mirtaceae (Eugeniasp.) and family Malvaceae (= Bombacaceae), (Ceiba samauma) and a species of Liliópsida of the family Arecaceae (Phoenix sylvestris). The taxa identified in the study area consist of tropical climate plants that thrived in lowland tropical forests, which rose by orogenesis to their current altitude (2400-2755 masl).